2013
DOI: 10.1063/1.4817854
|View full text |Cite
|
Sign up to set email alerts
|

Wave operators, similarity and dynamics for a class of Schrödinger operators with generic non-mixed interface conditions in 1D

Abstract: We consider a simple modification of the 1D-Laplacian where non-mixed interface conditions occur at the boundaries of a finite interval. It has recently been shown that Schrödinger operators having this form allow a new approach to the transverse quantum transport through resonant heterostructures. In this perspective, it is important to control the deformations effects introduced on the spectrum and on the time propagator by this class of non-selfadjont perturbations. In order to obtain uniform-in-time estima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…in [2], [7], [3]). Using specific spectral assumptions, a small-θ expansion for the modified dynamical system e −itH h θ , similar to the one given in [9], has been obtained in this case (see Theorem 4.4 in [10]); nevertheless, when both h and θ are small, the resulting error term is small uniformly in time only for initial states belonging to an appropriate subspace with prescribed energy conditions. This prevents to extend the result to the most relevant case of time dependent potentials.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…in [2], [7], [3]). Using specific spectral assumptions, a small-θ expansion for the modified dynamical system e −itH h θ , similar to the one given in [9], has been obtained in this case (see Theorem 4.4 in [10]); nevertheless, when both h and θ are small, the resulting error term is small uniformly in time only for initial states belonging to an appropriate subspace with prescribed energy conditions. This prevents to extend the result to the most relevant case of time dependent potentials.…”
Section: Introductionmentioning
confidence: 84%
“…In the case h = 1, it has been shown that the interface conditions (1.1) do not modify the spectrum provided that θ is small (see [9,Proposition 2.6]). In the present case, the dilation: y = (x − (b + a) /2) /h transforms the boundary conditions (1.1) into…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, H h > 0, it has been shown that H h θ has a purely continuous spectrum coinciding with R + , provided that θ is small (depending on h; see [14]). A detailed analysis concerned with operators of this class has been developed (in a slightly more general framework) in [8]- [15].…”
Section: A Modified Modelmentioning
confidence: 99%
“…The generalized eigenfunctions of H h θ , next denoted with ψ h θ (·, k, V h ), solve of the boundary value problem (we refer to [14]- [15])…”
Section: The Quantum Evolution Problemmentioning
confidence: 99%